THE ANALYSIS OF WORD ORDER IN NOUN PHRASE USED BY THE EIGHTH GRADERS OF SMP MUHAMMADIYAH 6 KRIAN IN WRITING DESCRIPTIVE TEXT (RETAIN, 2016)
THE ANALYSIS OF WORD ORDER IN NOUN PHRASE USED BY THE EIGHTH GRADERS OF SMP MUHAMMADIYAH 6 KRIAN IN WRITING DESCRIPTIVE TEXT Viky Kharisma Pratama English Education, Faculty of Languages and Arts, State University of Surabaya Email: vikykharisma11@yahoo.com Esti Kurniasih, S.Pd., M.Pd. English Education, Faculty of Languages and Arts, State University of Surabaya Email: estikurniasih87@yahoo.com Abstrak Sebagai komunikasi tertulis, menulis adalah salah satu keterampilan yang penting dan berguna yang harus dikuasai selain mendengar, berbicara, dan membaca. Di dalam kelas menulis yang sebenarnya, masih banyak pelajar bahasa asing yang mengalami kesulitan di dalam menulis, terutama di dalam menulis teks deskriptif. Dikarenakan menulis sebagai keterampilan yang rumit, di dalam proses menulis siswa mungkin melakukan kesalahan akibat dari penguasaan bahasa dan pemahaman mereka terhadap bahasa yang ditarget.Penelitian ini bertujuan untuk mengetahui jenis-jenis kesalahan yang siswa perbuat dan faktor-faktor apa saja yang mempengaruhi kesalahan mereka. Penelitian ini dilakukan di SMP Muhammadiyah 6 Krian. Subyek penelitian ini adalah siswa kelas delapan (8D). Jenis-jenis kesalahan diperoleh dari tulisan teks deskriptif dari siswa itu sendiri.. Penelitian kualitatif deskriptif digunakan untuk mengumpulkan data dan menjawab pertanyaan penelitian. Data didapatkan di dalam dua pertemuan. Jenis-jenis kesalahan dikategorikan berdasarkan taksonomi Corder. Penemuan memperlihatkan bahwa sebagian besar siswa mengalami kesalahan yang pra-sistematis dan kesalahan yang sistematis. Lebih lanjut lagi, terdapat dua faktor yang mempengaruhi kesalahan-kesalahan siswa: (1) penerjemahan dan (2) kesalahan intralingual. Kata Kunci: analisis tentang susunan kata, eror, frasa kata benda, menulis, teks deskriptif. Abstract As a written communication, writing is one of the important and useful skills to be mastered besides listening, speaking, and reading. In the real writing class, there are still many foreign language learners who encounter difficulties in writing, especially in writing descriptive text. As writing is a complex skill, in the writing process the students are probably making errors as the result of their language acquisition and their understanding of the target language. This study aims to find out what kinds of errors that the students make and what factors influence their errors. This study took place in SMP Muhammadiyah 6 Krian. The subjects of the study are the eight grade students of D class. The kinds of errors and the factors that caused the errors were elicited from the students’ self-written descriptive text. Descriptive qualitative research was employed to compile the data and answer the research questions. The data were obtained in two meetings. The errors were categorized based on Corder’s taxonomy. The findings show that most of the students had pre-systematic error and systematic errors. Furthermore, there were two factors that influence the students’ errors: (1) translation and (2) intralingual errors. Keywords: analysis of word order, error, noun phrase, writing, descriptive text